Flood management and mitigation programme :Working Paper: Legal Aspects of the Mandate of the 1995 Mekong Agreement for Enhancing Cooperation in Addressing Transboundary Flood and Related Issues – October 2007. (MRC, 2020)
Sách do Ủy ban Mê Công tài trợ